The Major Chromoblastomycosis Etiologic Agent Fonsecaea pedrosoi Activates the NLRP3 Inflammasome - Castro, Raffael Júnio Araújo de; Siqueira, Isaque Medeiros; Jerônimo, Márcio Sousa; Basso, Angelina Maria Moreschi; Veloso Junior, Paulo Henrique de Holanda; Magalhães, Kelly Grace; Leonhardt, Luiza Chaves; Oliveira, Stephan Alberto Machado de; Bürgel, Pedro Henrique; Tavares, Aldo Henrique; Bocca, Anamélia Lorenzetti (Frontiers in Immunology, 2017)
Fonsecaea pedrosoi is the main etiologic agent of chromoblastomycosis (CBM), one of the most prevalent subcutaneous mycosis in tropical and subtropical countries. CBM is a poorly characterized chronic infection that commonly starts after transcutaneous inoculation of conidia and saprophytic hyphae of F. pedrosoi. Recently, we have shown that unlike conidia, hyphae and muriform cells (the parasitic morphotype) of F. pedrosoi promotes an intense inflammatory response pattern in vivo which comprises the production of a inflammasome-derived cytokine, IL-1β. Nonetheless, the mechanisms underlying IL-1β production and maturation upon F. pedrosoi infection and its functional output in the course of CBM remains unknown. We show here that F. pedrosoi hyphae, differently from conidia, induce IL-1β secretion in both bone marrow-derived dendritic cells and macrophages. Using inhibitors and knockout cells, we demonstrated that the mechanisms underlying IL-1β production by hyphae-infected macrophages were dependent on dectin-1, -2 and -3 receptors and the Syk-NF-kB signaling pathway. Furthermore, F. pedrosoi promoted a NLRP3-dependent inflammasome activation, which required potassium efflux, reactive oxygen species production, phagolysosomal acidification and cathepsin B release as triggers. IL-1β processing and release was mediated primarily by caspase-1 and, to a lesser extent, by caspase-8 dependent cleavage. Finally, we showed using a murine CBM model that F. pedrosoi elicits a NLRP3-regulated IL-1β and IL-18 release in vivo, but without NLRP3 inflammasome activation interfering in the course of the experimental infection.